Association between Pre-Conception Health and Nutrition Knowledge- Attitude-Practice and Anemia among Pre-Marital Women in Sleman, Indonesia - Ansari, Muhammad Ridwan; Putri, Febriani; Nangley, Wulan; Kandarina, Bernadette Josephine Istiti (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
The study aimed to assess the association between pre-conception health and nutrition Knowledge-Attitude-Practice (KAP) and anemia among Pre-Marital Women (PMW). In this cross-sectional study, Mid-Upper Arm Circumference (MUAC) measurement, 24-hour food recall interview, blood sample collection, and validated KAP questionnaire interview were conducted to 111 PMW in Sleman in 2021. The study found that 21.6%, 14.4%, and 49.1% of PMW had Chronic Energy Deficiency (CED), anemia, and lack of minimum dietary diversity, respectively. The proportions of PMW with adequate KAP were 70.5%, 67.8%, and 64.3%, respectively. Pre-conception health and nutrition practices are associated with anemia (p<0.05), but knowledge and attitude are not.